TINJAUAN YURIDIS TERHADAP EFISIENSI PERUSAHAAN SEBAGAI ALASAN PEMUTUSAN HUBUNGAN KERJA - Abdul Rasyid Lukman Siregar; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Companies in carrying out their operational activities often deal with economicproblems and market conditions that cause companies to suffer losses so that it is necessaryto take efficiency measures to maintain the continuity of the company's operations. One formof efficiency that is often done by employers is to reduce the number of workers byterminating employment.This research is a Normative legal research, which is a library research thatexplains the principles of law such as applicable laws and regulations and is associated withlegal theories related to the problem under study. This research was conducted to find outhow the concept of termination of employment is regulated in Article 164 Paragraph (3) ofLaw Number 13 of 2003 concerning Employment on the Decision of the Constitutional CourtNumber 11 / PUU-IX / 2011, how to review cases of termination of employment for reasonsof company efficiency, and how legal protection and justice in termination of employment aredue to reasons of company efficiency.The conclusion of this research is, First, the word